A Scoping Review of School-Based Nutrition Education Interventions in the Islamic Republic of Iran. - Aboul-Enein, Basil H.; Gambescia, Stephen; Keller, Teresa; Benajiba, Nada; Kelly, Patricia J. (Journal of School Nursing, 2026)
This scoping review aims to identify evidence-based school nutrition interventions for implementation in Iran's dynamic economic, cultural, and socio-political environment. A review of published studies (2004-August 2024) using the PRISMA-ScR guidelines across 14 databases was conducted. The efficacy of various interventions reported significant positive changes at multiple levels: anthropometric, biological, and knowledge, attitudes, and behaviors related to healthy eating and lifestyle. Investigators carrying out research on "what works" in school-based nutrition education and general healthy lifestyle programs and services in the Islamic Republic of Iran have a host of challenges; however, much more research needs to be done. While there are few studies in this area of inquiry, outcomes on the nutrition interventions to date are impressive. The major challenges in improving school-based nutrition programs include the education of young women, establishing national standards for school food programs and education, and strategic advocacy by stakeholders to improve nutrition education in schools in Iran.